2009
DOI: 10.1007/s11999-008-0684-7
|View full text |Cite
|
Sign up to set email alerts
|

Suspension Suture Augmentation for Repair of Coracoclavicular Ligament Disruptions

Abstract: Surgical reconstruction of the coracoclavicular ligament is a fundamental part of management of highgrade acromioclavicular dislocations and Type II lateral third clavicular fractures. However, no single surgical procedure is fully satisfactory because of failure or complications. We present an alternative coracoclavicular stabilization technique, which avoids the use of hardware or tendon graft, that was used in 10 consecutive patients with complete coracoclavicular ligament disruptions. These patients were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 23 publications
(69 reference statements)
0
21
0
Order By: Relevance
“…15,56 A recent retrospective study reviewed 10 patients with a complete CC ligament disruption who were each treated with two #5 Ethibond sutures (Ethicon, Somerville, NJ) placed through drill holes in the clavicle and looped around the coracoid process. 40 This technique afforded good functional outcomes and no loss of reduction at a minimum follow up of 14 months (average, 34.8 months). 40 At 12 months after surgery, the mean University of CaliforniaeLos Angeles shoulder rating score was 33.8 points, and the mean Western Ontario Shoulder Instability Index aggregation score was 93.4 points.…”
Section: Ca Ligament Transfermentioning
confidence: 86%
See 2 more Smart Citations
“…15,56 A recent retrospective study reviewed 10 patients with a complete CC ligament disruption who were each treated with two #5 Ethibond sutures (Ethicon, Somerville, NJ) placed through drill holes in the clavicle and looped around the coracoid process. 40 This technique afforded good functional outcomes and no loss of reduction at a minimum follow up of 14 months (average, 34.8 months). 40 At 12 months after surgery, the mean University of CaliforniaeLos Angeles shoulder rating score was 33.8 points, and the mean Western Ontario Shoulder Instability Index aggregation score was 93.4 points.…”
Section: Ca Ligament Transfermentioning
confidence: 86%
“…40 This technique afforded good functional outcomes and no loss of reduction at a minimum follow up of 14 months (average, 34.8 months). 40 At 12 months after surgery, the mean University of CaliforniaeLos Angeles shoulder rating score was 33.8 points, and the mean Western Ontario Shoulder Instability Index aggregation score was 93.4 points. The study excluded 2 patients treated surgically (including 1 who had sustained a coracoid fracture) because of loss to follow-up.…”
Section: Ca Ligament Transfermentioning
confidence: 86%
See 1 more Smart Citation
“…Dating back to the work of Neer and other earlier reports, 22% to 33% of Neer type II distal clavicle fractures fail to heal with nonoperative treatment, and an additional 45% to 67% require more than the traditional 3 months for the fracture to heal. 4,10,[15][16][17][19][20][21][22]26,28 However, in older patients with more osteoporotic bone, there is a concern that surgical intervention can lead to operative complications. Several authors have reported acceptable results with nonoperative treatment in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…11,14,23 Although the current literature describes many procedures for the treatment of these unstable fractures, there has been no consensus or gold standard determined, and many of the treatment options have high complication rates. 13,15,16 Currently, the most widely used options for surgical fixation of these fractures are (1) a soft tissue reconstruction/repair with heavy suture, 10,17,26,31 (2) internal fixation with a plate and screw construct, 1,9 or (3) a Hook plate construct. 2,[5][6][7]12 However, these treatment options are still fraught with complications, and again the decision for treatment choice is very subjective.…”
mentioning
confidence: 99%